Determinants of Private Investment: Time Series Evidence from Bangladesh - Hassan, A.; Salim, Ruhul (Western Illinois University, 2011)
This article examines the determinants of private investment in Bangladesh using the standard time series econometric analysis. The empirical results partially support the flexible accelerator hypothesis. It is partial in the sense that real interest rate is not statistically significant in determining private investment whereas national output is very much effective in the long run. Further, government expenditure is found to be a significant determinant of private investment, both in the long- and short run. Government expenditures crowd out private investment, however, the effect is minimal as the investment is not interest responsive. Thus, government expenditure can be used effectively to lift output in case of recession while monetary policy is not so effective in recession because reducing the interest rate investment cannot be increased.